Optical fibre long period grating sensors with nanostructured coatings - Topliss, Stephen M. (Cranfield University, 2011)
The dual resonant response of long period fibre gratings (LPG) operating near the phase matching turning point to the deposition of nanostructured coatings is explored. A broad range of LPGs have been fabricated with grating periods ranging from 80m to 180m, and these have been characterized with three different coating materials,-tricosensoic acid, undecyl-calix[4]resorcarene and tert-butyl-calix[8]arene carboxylic acid. The dual resonant response has been exploited with the construction of an LPG based sensor coated with a quinolinium dye forming a pH sensor. The wavelength response of this device was measured with a sensitivity of -0.55pH/nm. Furthermore, length apodised phase shifted long period gratings have been characterized, and the effect on the dual resonant response has been recorded. Partial coating of this device has resulted in the observation of a bandgap feature in the wavelength response. The use of calixarenes as a functional coating for long period fibre gratings is also investigated. Calixarene is applied in a thin layer with a thickness of several hundred nm’s to the cladding of the fibre in the region containing the LPG sensor. The chemical sensing capabilities of a long period fibre grating sensor is presented for the detection of the volatile organic compounds; hexane, cyclohexane, benzene and toluene. The wavelength response was measured and the sensitivity to toluene vapour was recorded at 1600ppmv/nm. Using intensity detection of the central maxima in the wavelength response, the chemical selectivity is demonstrated showing sensitivity to toluene vapour over 13 times greater compared to hexane vapour.